Pengembangan Buku Ajar IPS Terpadu Berbasis Kontekstual pada Tema Keadaan Alam dan Aktivitas Penduduk di Indonesia - Harefa, Marlina; Rusdy A. Siroj; Siti Julaeha (Jurnal Serambi Ilmu, 2025)
This developmental research produced a contextual-based integrated social studies (IPS) textbook focused on the theme of natural conditions and population activities for seventh-grade students at SMP Negeri 2 Pagar Alam. The textbook development followed the Dick and Carey model, encompassing stages of needs analysis, design, development, and formative evaluation, including self-evaluation, expert review, one-on-one evaluation, small group evaluation, and field testing. Expert validation confirmed that the textbook is valid and suitable for use after revisions based on expert feedback. Practicality evaluation during the small group phase received positive responses, with an average score of 80.95%. The effectiveness of the textbook was demonstrated by a significant improvement in students’ learning outcomes, indicated by an N-gain score of 0.76 (high category), alongside a high average student engagement rate of 85.85%. This contextual-based IPS textbook is effective in enhancing students’ conceptual understanding and learning outcomes related to the theme of natural conditions and population activities.